TEACHERS OF PHYSICAL EDUCATION (Fiep Bulletin - online, 2017)
This research aims to identify the beliefs that influence the pedagogical practice of school dance teaching. In order toachieve this, quantitative and qualitative research was carried out based on the case study, exploratory and cross-sectional. Forthe data collection, the instrument was used questionnaires, applied to 17 physical education teachers who work in the highschool of public schools. Among the results obtained is the belief that physical education as a discipline capable of promoting theintegral formation of the student, the belief that new strategies contribute considerably to the student's learning with difficulties incertain contents, belief that content dance is Accessible to all learners. It was also verified that most of the teachers use the dancecontent in the daily classes, have a good knowledge about the educational beliefs and the school dance, emphasizing that, theseteachers are supported in their beliefs - attitudes, values, opinions, Preconceptions, perceptions, ideologies and teachingexperience - which allows us to infer that the teaching culture of physical education teachers, especially with regard to theirbeliefs, positively influence the pedagogical practice of school dance teaching.